COAGULATION FOR TREATMENT OF SWINE SLAUGHTERHOUSE WASTEWATER - Bui, Ha Manh; Duong, Huong Thi Giang (GeoScience Engineering, 2017)
In this study, wastewater taken from Nam Phong swine slaughterhouse, Ho Chi Minh City, was used to evaluate treatment efficiency of common coagulants, including Alum (Aluminum Sulfate - Al2(SO4)3.18H2O), Poly-Aluminum Chloride (PAC) and Ferrous Sulfate (FeSO4.7H2O), using Jar-test system. Experiments were conducted using one-factor-at-a-time method to examine three variables: pH, stirring speed and coagulant dosages. The results show that both Alum and PAC perform over 90% removal of color, turbidity, COD and total phosphor from slaughterhouse wastewater at pH 7 with a stirring speed of 75 revolutions per minute (RPM) and average coagulant dosages (450 mg/L for Alum and 550 mg/L for PAC). Meanwhile, in the appropriate conditions at pH 10 and 75 RPM with a chemical dosage of 350 mg/L, COD and total phosphor (TP) removal efficiencies by Ferrous Sulfate exceed 87%, but those of turbidity and color only reach 25%. This finding could be a promising coagulation method as a pretreatment or adding method to swine slaughterhouse wastewater.